Abu Yusuf's Fiscal Thought in the Book of Al-Kharaj and Its Relevance to the Modern Public Financial System - Ratna Resa Rosita; Wianda Saskya; Ana Fauziya Diyana; Lina Marlina (Al Urwah : Sharia Economics Journal, 2025)
Classical fiscal thought in Islamic economic literature has rarely been examined comparatively within the framework of contemporary public finance theory. This study aims to analyze Abu Yusuf's fiscal framework in Buku al-Kharaj and evaluate its relevance to modern public finance systems. A qualitative method was employed using library research and content analysis of the primary text al-Kharaj, complemented by conceptual comparison with contemporary fiscal theory. The findings indicate that Abu Yusuf's fiscal thought emphasizes distributive justice, proportional taxation, revenue optimization based on productivity, and accountability in fiscal governance. The productivity-based kharaj system and supervision of tax administration demonstrate normative correspondence with the principles of equity, efficiency, and fiscal sustainability in modern public finance. Theoretically, these findings contribute to the integration of classical Islamic economics and contemporary fiscal studies. Practically, Abu Yusuf's framework may serve as a normative reference for equitable tax reform and responsible public financial governance.